Comparing different scaling methods for monitoring weightlifting performance - Slaton, J. (Electronic Theses and Dissertations. Paper 3984, 2020)
Physiological performance has been commonly scaled for body size using various methods to scale anthropometrics, but a paucity of data exists on scaling muscle size. The aim of this thesis was to elucidate the optimal method to scale height (HT), body mass (BM), lean body mass (LBM), and muscle cross-sectional area (CSA) when scaling weightlifting performance for body size. 26 weightlifters (13 male, 13 female) participated in this study. The measurements collected were the snatch (SN), clean and jerk (CJ), isometric peak force (IPF), and countermovement jump height (CMJH). HT, LBM, BM, and vastus lateralis CSA were scaled using the ratio standard and allometry. Competition performance scaled for allometrically scaled CSA possessed greater relationships to CMJH (r = 0.60 - 0.78) than the ratio standard (r = 0.56 - 0.58). These findings suggest that allometrically scaling CSA may be superior when scaling weightlifting performance for CSA.